THE ROLE OF THE LOCAL GOVERNMENT POLICY IN ERADICATION OF CHRONIC ENERGY IN GORONTALO DISTRICT - Zuriati Muhamad; Salahudin Liputo (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2017)
In Indonesia, the problem of Chronic Energy Deficiency in pregnant women is still very high at 46.6% in 2014 according to RISKESDAS. Similarly in Kabupaten Gorontalo the prevalence rate of Chronic Energy Deficiency in pregnant women in 2014 reached 14.4%. So that requires the attention of the government to overcome it. This study aims to identify SEZ problems in pregnant women and determine the policy strategy and steps taken by the government of Gorontalo Regency in overcoming SEZ problems in pregnant women. The research method used is qualitative research with Ethnography approach. Data were collected by in-depth interviews with Head of Health Division of Mother of Child of Gorontalo District Health Office, Head of Tilote and Pulubala Health Center and village midwife in two puskesmas. The result of interview shows that the main cause of SEZ occurrence in pregnant women is pregnant women's diet, behavior that is still lacking in maintaining health, low family income, knowledge and education which is still low, and distance of pregnant mother less than 2 years. Efforts that have been made Dinas Kesehatan Kab. Gorontalo in tackling the problem of KEK in pregnant mother that is by existence of Program of First Life Day (HPK) with supplementary feeding (Fertilizer), milk and FE tablet to prevent anemia and keep doing Information Communication and Education to pregnant mother, Family and Community to keep maintain a good nutrition intake, maintain a healthy lifestyle and improve health services to the community.Keywords : Government policy; KEK; pregnant mother